A New Phenyl Derivated Butyrolactone from Fermentation Products of Endophytic Fungus Aspergillus terreus - Zhou, Kun; Wang, Yuede; Dong, Wei; Ji, Bing-Kun; Ye, Yanqing; Du, Gang; Li, Yinke; Gao, Xuemei; Hu, Qiufen; Yang, Haiying (Asian Journal of Chemistry, 2015)
A new phenyl derivated butyrolactone, terrephenol C (1) was isolated from the fermentation products of a fungus Aspergillus terreus. Its structure was elucidated by spectroscopic methods, including extensive 1D NMR and 2D NMR techniques. The antitobacco mosaic virus (anti-TMV) activity of 1 was evaluated and showed anti-TMV activity with inhibition rates of 16.7 %.